2013
DOI: 10.1080/15402002.2012.688779
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphy Reliability with Normal Sleepers

Abstract: We found that missing data was a significant problem for long-term assessment of sleep using actigraphy. We suggest that researchers consider compensatory strategies, such as extending the assessment period and using adjunctive measures, in order to obtain sufficient data for analysis. We also recommend that future improvements in actigraphy instruments should aim to address the sources of missing data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 11 publications
2
13
0
Order By: Relevance
“…In a medication adherence study of a predominantly middle-aged community sample (N ¼ 48; 36 -87 years), there was a linear increase in omission errors over two months of investigation (Morrell, Park, Kidder, & Martin, 1997). Similarly, in an actigraphy study with a middle-aged sample (N ¼ 60; 35-65 years of age), missing data were shown to increase over a period of five weeks (Ustinov & Lichstein, 2013). PM performance in a time-logging task was also shown to decrease over days within one week, although this effect was reported as small and observed predominantly in younger participants (in their 20s), rather than in the older age groups (60s or 80+; Rendell & Thomson, 1999).…”
Section: Introductionmentioning
confidence: 87%
“…In a medication adherence study of a predominantly middle-aged community sample (N ¼ 48; 36 -87 years), there was a linear increase in omission errors over two months of investigation (Morrell, Park, Kidder, & Martin, 1997). Similarly, in an actigraphy study with a middle-aged sample (N ¼ 60; 35-65 years of age), missing data were shown to increase over a period of five weeks (Ustinov & Lichstein, 2013). PM performance in a time-logging task was also shown to decrease over days within one week, although this effect was reported as small and observed predominantly in younger participants (in their 20s), rather than in the older age groups (60s or 80+; Rendell & Thomson, 1999).…”
Section: Introductionmentioning
confidence: 87%
“…Therefore, some studies reported that sleep latency is the most unreliable sleep parameter measured by actigraphy. 27,28 Furthermore, a meta-analysis using polysomnography found that the ADHD patient group and the control group were not significantly different in terms of sleep latency. Polysomnography measures the time of sleep latency to sleep stage 2, using the results of EEG, electrooculography, and electromyography, while actigraphy measures sleep latency as the time from lying in bed or turning off the light to the first epoch of inactivity of at least 10 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, actigraphy-based sleep parameters are closely correlated with polysomnography results. 27,28 Sleep restrictions or sleep disturbance in ADHD patients could lead on to neurobehavioral dysfunction, especially vigilance and attention. [29][30][31] Also, topographical electroencephalogram (EEG) study showed neuromaturational delay in ADHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well accepted that the use of actigraphy is best validated in normal sleepers, 54 we contend that it is a preferable tool to use in pregnant women. Based on our data, it appears that pregnant women fall into the category of "normal sleepers" rather than "abnormal sleepers," i.e.…”
mentioning
confidence: 99%
“…This is important to acknowledge since length of data collection correlates with degree of intra-individual variability. 54 The concomitant use of diaries and actigraphy affords the opportunity to comment on the use of actigraphy in pregnant women.…”
mentioning
confidence: 99%